Early Chronic Carbamazepine-in-Food Administration to MAM/Pilocarpine Rats Does Not Affect Convulsive Motor Seizures - Nobili, Paola; Cattalini, Alessandro; de Grazia, Ugo; Cagnoli, Cinzia; de Curtis, Marco; Battaglia, Giorgio Stefano; Colciaghi, Francesca (Frontiers in Pharmacology, 2020)
Antiepileptic drug-resistance is a major health problem in patients with cortical dysplasia (CD). Whether drug-resistant epilepsy is associated with progressive brain damage is still debated. We previously generated a rat model of acquired CD, the methylazoxymethanol-pilocarpine (MP) rat, in which the occurrence of status epilepticus and subsequent spontaneous seizures induce progressive brain damage (Nobili et al., 2015). The present study tested the outcome of early-chronic carbamazepine (CBZ) administration on both seizure activity and brain damage in MP rats. We took advantage of the non-invasive CBZ-in-food administration protocol, established by Ali (2012), which proved effective in suppressing generalized convulsive seizures in kainic acid rat model of epilepsy. MP rats were treated immediately after the onset of the first spontaneous seizure with 300 mg/kg/day CBZ formulated in pellets for a two-months-trial. CBZ-treated rats were continuously video-monitored to detect seizure activity and were compared with untreated epileptic MP rats. Despite CBZ serum levels in treated rats were within the suggested therapeutic range for humans, CBZ affected spontaneous convulsive seizures in 2 out of 10 treated rats (responders), whereas the remaining animals (non-responders) did not show any difference when compared to untreated MP rats. Histological analysis revealed cortical thinning paralleled by robust staining of Fluoro-Jade+ (FJ+) degenerating neurons and diffuse tissue necrosis in CBZ-non-responder vs CBZ-responder rats. Data reported here suggest that MP rat model represents suitable experimental setting where to investigate mechanisms of CD-related drug-resistant epilepsy and to verify if modulation of seizures, with appropriate treatment, may reduce seizure-induced brain damage.